Investigation of the effects of fans' club image perceptions and fan group membership status on sports consumption behaviors - Sercan Kural; Ismail Karatas (ROL Spor Bilimleri Dergisi)
This research was carried out to examine how Ankaragücü and Gençlerbirliği fans' perceptions of club image and being a member of a fan group affect their sports consumer behavior. This quantitative investigation employed the correlational research model in accordance with the general purpose of the research. The study group of the research consists of 193 participants, 122 of which are Ankaragücü fans and 71 Gençlerbirliği fans. Convenience sampling, one of the non-probabilistic sampling methods, was used as a sampling method. Further, a scale form that comprised three parts was used as the data collection tool. The first part of the scale form was the “Personal Information Form,” the second part comprised the “Sports Consumption Behaviors Scale,” and the third part involved the “Club Image Scale.” A regression analysis was used for a statistical evaluation. The results established that being part of a fans’ group have significant positive effects on the “intention to attend matches” and “media consumption intention” as well as on components of sports consumption behaviour but did not have a significant effect on the “intention to consume licensed products.” In addition, the present study found that club image did not have a significant effect on sports consumption behaviors. It can be said that being a member of a fan group influences on both the intention to attend the matches and the media consumption intention.